EFEKTIVITAS KINERJA TUTOR PROGRAM PENDIDIKAN KESETARAAN PAKET C DI SATUAN PENDIDIKAN NON FORMAL SANGGAR KEGIATAN BELAJAR KOTA PEKANBARU - Marsya Franitasari; Wilson Wilson; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effectiveness of Tutor Program Equivalency Education Performance Package C in Non-Formal Education Unit Pekanbaru City Learning Activity Center. This research uses descriptive research with qualitative approach which aims to provide a systematic description of the Performance Effectiveness of Tutor of Equal Education Program Package C in Non-Formal Education Unit Pekanbaru City Learning Activity Center.As a reference to conduct research in the field, researchers prepare a grid in the form of questions to be presented interview materials to respondents. After the data collected, the researchers continue the analysis of research data. The results of research on the Performance Effectiveness of Tutor Program Equivalency Education Package C in Non-Formal Education Unit Pekanbaru City Learning Activity Center has been implemented effectively viewed from: 1) All the equivalent education programs C package education has been carrying out the main task and function of teaching equality education package C , 2) The process of educating citizens learning package C has been implemented with an emotional and interactive approach. Tutors have tips on teaching so that time can be optimized effectively. As for the tutor's tips by providing independent tasks to the residents learn to read more material provided through the internet or other sources. 3) Teach citizens learn the equivalence of C packets implemented with face-to-face at least 16 times. Using lecture methods, frequently asked questions and discussions. 4) The guidance process held is personal. The tutor carries out guidance to the learning community who needs more guidance. 5) Briefing given tutor to the citizens learn in the form of advice, motivation, and solutions so that the problems of learning citizens can be completed. The guidance system is given the same as guidance.Keywords: Effectiveness, Performance, Tutor, Package Equivalency Education Program C.